2016
DOI: 10.1111/1541-4337.12204
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids as Potent Scavengers of Hydroxyl Radicals

Abstract: Oxidative stress is a fundamental principle in the pathophysiology of many diseases. It occurs when the production of reactive oxygen species exceeds the capacity of the cell defense system. The hydroxyl radical is a reactive oxygen species that is commonly formed in vivo and can cause serious damage to biomolecules, such as lipids, proteins, and nucleic acids. It plays a role in inflammation-related diseases, like chronic inflammation, neurodegeneration, and cancer. To overcome excessive oxidative stress and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
191
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(205 citation statements)
references
References 120 publications
(206 reference statements)
7
191
0
7
Order By: Relevance
“…They have been considered as a secondary (non-enzymatic) reactive oxygen spe-cies scavenging system in plants and humans [36]. Flavonoids exhibit direct scavenging of reactive oxygen species [36] one of the ways scavenging reactive oxygen species, flavonoids can easily donate hydrogen atom. Thus, while reactive oxygen species are inactivated by flavonoids, flavonoids return to phenoxyl radical [37].…”
Section: Over Accumulation Of Flavonoid Versus Reactive Oxygen Speciementioning
confidence: 99%
“…They have been considered as a secondary (non-enzymatic) reactive oxygen spe-cies scavenging system in plants and humans [36]. Flavonoids exhibit direct scavenging of reactive oxygen species [36] one of the ways scavenging reactive oxygen species, flavonoids can easily donate hydrogen atom. Thus, while reactive oxygen species are inactivated by flavonoids, flavonoids return to phenoxyl radical [37].…”
Section: Over Accumulation Of Flavonoid Versus Reactive Oxygen Speciementioning
confidence: 99%
“…Our results also shown that flavonoids (kaempferol, myricetin, quercetin and luteolin glycosides) and phenolic acids (chlorogenic, neochlorogenic and caffeic acids) are associated with the antiradical activity. These compounds act as scavengers of various oxidizing species such as superoxide anion, hydroxyl radical or peroxy radicals and as quenchers of singlet oxygen [23] and their antiradical capacity arise from their ability to inhibit lipid peroxidation, chelate redox-active metals, and reduce all processes involving reactive oxygen species [24]. They may exert protection of cell structures through different mechanisms, and one in particular is their ability to increase the levels of the powerful intracellular antioxidant enzymes [25,26].…”
Section: Abts Radical Scavenging Activitymentioning
confidence: 99%
“…Phenolic compounds can act as visual signals for attracting pollinating insects, phytoalexins, photoreceptors, detoxifying agents, scavenger of reactive oxygen species (ROS) such as H 2 O 2 , hydroxyl, peroxyl or alkoxyl radical; they also, contribute to different flavours and colour shades in flowers, leaves, fruits and vegetables, protect the plant cells against UV radiation, fungal, bacterium or virus pathogens, parasites and herbivores, etc. [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are present in all part of the plants, especially the photosynthesising plant cells of a wide range of vascular plants; up to date over 8000 flavonoid compounds have been identified and the number is still increasing. Chemically, they all have characteristic C 6 -C 3 -C 6 benzo--pyrone skeleton consists of two benzene rings (A and B, Table 1) connected through heterocyclic pyran ring (C) [5,6,8,17]. Flavonoids generally, occur in plants as glycosides (O-glycoside or C-glycoside) with a monosaccharide or disaccharide attached, but also as aglycones or methylated and sulfated derivatives [9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation